Lex Mosaica;: or, The law of Moses and the higher criticism - French, Richard Valpy (Eyre & Spottiswoode, 1894)
The archaeological witness to the literary activity of the Mosaic age, by A.H. Sayce: Moses the author of the Livitical code of laws, by G. Rawlinson: The Deuteronomical code, by G.C.M. Douglas: Period of Joshua, by R.B. Girdlestone: Period of the judges, by R.V. French: The times of Samuel and Saul, by J.J. Lias: The period of David and Solomon, by F. Watson: The northern kingdom, by J. Sharpe: The history of the southern kingdom in relation to the law of Moses, by A. Stewart: The eighth century, by S. Leathes: The seventh century, by R. Sinker: Ezekiel and the priestly school, by F.E. Spencer: The post-exilic period, by R. Watts: Summary, by H. Wace.